EVALUATION OF METABOLIC SYNDROME AND OBESITY IN WOMEN WITH BREAST CANCER TREATED IN A SERVICE WITH INTERDISCIPLINARY ATTENTION: A PROSPECTIVE COHORT - Prado, Vanildo; Buttros, Daniel Araújo Brito; Pessoa, Eduardo Carvalho; Pessoa, Eduardo Carvalho; Vespoli, Heloísa Maria Lucca; Nahás, Eliana Aguiar Petri (Mastology, 2021)
Introduction: Patients with breast cancer have a higher risk of gaining weight and of presenting with metabolic syndrome (MS), with worsening overall and specific survival. Intervention from an interdisciplinary team can influence the prognosis. Objective: To evaluate the occurrence of metabolic syndrome and its components in women during the first year after diagnosis of breast cancer. Methods: Prospective, single-centered clinical study that included women with a recent diagnosis of breast cancer, age ≥40 years, histological diagnosis of breast cancer, without metastatic disease and without established cardiovascular disease (CVD). Clinical and anthropometric data (blood pressure, body mass index [BMI] and waist circumference) were collected through interviews and physical examination. For biochemical analysis, HDL, triglycerides (TG) and glucose were requested. Women with MS were considered to have three or more diagnostic criteria: waist circumference (WC)>88 cm; TG³150 mg/dL; HDL<50 mg/dL; blood pressure ³130/85 mmHg; glucose ³100 mg/dL. The measurements were carried out in three moments: first cancerconsultation (T0m), six months (T6m) and 12 months (T12m). The patients underwent interdisciplinary evaluation and monitoring (nutritional and psychologi- cal), according to the service’s routine. For statistical analysis, the McNemar test was used to compare the moments and the χ2 test of trend. Results: Seventy two women with breast cancer were included, with a mean age of 58.4 ±10.7 years and 83.3% in the post-menopause. The cancer profile of the patients was that of an early-stage disease (94.4% stage I and II) with a favorable immunohistochemical profile (79.1% positive estrogen receptor, 72.2% positive progesterone receptor and 86.1% HER2 negative). In the assessment of MS, no differences were observed in the occurrence between the three moments, with 37.5% of patients with MS at diagnosis, 43% at 6 months and 44.4% at 12 months (p=0.332). A significant difference was observed in the occurrence of hypertriglyceridemia (TG³150 mg/dL) of 25% in T0m, 36.1% in T6m and 44.4% in T12m (p<0.05). There was no increase in obesity criteria (BMI ³ 30 mg/m2 and waist circumference / WC>88 cm) in the studied period, with mean BMI of 28.9 kg/m 2, 28.8kg/m2 and 28.8 kg/m 2 and WC equal 97.2 cm, 97.2 cm and 96.7 cm, at T0, T6 and T12 moments, respectively (p>0.05). When comparing the individual MS criteria between the three assess - ment moments, there was only a statistical difference in the triglyceride and glycemia criteria. The analysis of glycemia showed a decrease in mean values, from 106.6 mg/dL in T0m, 100.4 mg/dL in T6m and 98.9 mg/dL in T12m (p=0.004). Regarding TG, an increase in mean values was observed, from 121 mg/dL in T0m, 139.4 mg/dL in T6m and 148.4 mg/dL in T12m (p=0.003). Conclusion: Women with breast cancer submitted to interdisciplinary evaluation did not show an increase in the occurrence of MS during the first year after cancer diagnosis. Among the components of MS, there was a reduction in blood glucose values and an increase in triglyceride values.